Penggunaan Metode Cerdas Cermat untuk Meningkatkan Hasil Belajar Siswa pada Materi Hutang Piutang, Gadai, dan Hiwaalah di Kelas IX-6 MTs Negeri 2 Kota Bima - Siti Nurrahmah (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
This research is based on the low learning outcomes of students in learning Jurisprudence in class IX-6 semester 2 of the 2021/2022 academic year at MTsN 2 Kota Bima, on the material Debts, mortgages and hiwaalah. One alternative technique to improve learning outcomes is the quiz technique. The purpose of this study was to get an overview of the goals regarding improving learning outcomes through meticulous techniques on debt, mortgage and hiwaalah materials in class IX-6 students in semester 2 of the 2021/2022 academic year at MTsN 2 Kota Bima. This type of research is classroom action research carried out in 2 cycles, each cycle consisting of planning, action, observation, and reflection stages. The data obtained in this study were the results of cycle I and cycle II tests. From the results of this research action, it can be seen from the class average value before the study of 60.50 in cycle I to 71.50, an increase in cycle II of 80.50. This average value already meets the criteria for research success on an average point of learning completeness of 70. For the proportion of classical completeness of a number of 20 students from before the research was 45.00%, in cycle I became 65.00%, increased in cycle II of 85.00%. This value already meets the research completeness criteria at the point of limiting the proportion of classical learning mastery of 70%. So from all the implementation of action research activities in class IX-6 semester 2 of the 2021/2022 school year at MTsN 2 Kota Bima, it can be concluded that through meticulous techniques can improve student learning outcomes in the subject matter of debts, mortgages and hiwaalah in class IX- 6 semesters 2 of the 2021/2022 academic year at MTsN 2 Kota Bima.